Analysis of influencing factors of seawater intrusion in the Yangtze River Estuary and control for water supply security - Chen, Yubin; Xu, Yuni; Chen, Guiya; Zeng, Ming; Zhang, Tao; Zhang, Xiao; Zhang, Yu (Frontiers in Marine Science, 2024)
Seawater intrusion poses a significant threat to the water supply of coastal cities both presently and in the future. It is crucial to identify the controllable factors influencing seawater intrusion, both natural and anthropogenic, in order to ensure water supply security. This study examined seawater intrusion characteristics using monitoring data from 1994 to 2019. Factors such as daily flow rate, duration of intrusion, water quality, and tidal level were analyzed to establish correlations and identify the primary influencing factors in the Yangtze River Estuary. The findings reveal that seawater intrusion in this area is most prevalent from November to April, peaking in February and March. The key controllable factors affecting chloride levels at the intake are the daily flow rate at Datong Station and the tidal range at Xuliujing Station. Additionally, the study proposes control methods to safeguard water supply, including providing daily flow rate values for flushing seawater intrusion at Datong Station under different tidal ranges and intrusion durations. These research results provide valuable guidance for the emergency operation of the Three Gorges-centered reservoir group against seawater intrusion.